XRD Identification of Ore Minerals during Cruises: Refinement of Extraction Procedure with Sodium Acetate Buffer - Milinovic, Jelena; Dias, Ágata; Janeiro, Ana I.; Pereira, Manuel F. C.; Martins, Sofia; Petersen, Sven; Barriga, Fernando J. A. S. (Minerals, 2020)
The on-board identification of ore minerals during a cruise is often postponed until long after the cruise is over. During the M127 cruise, 21 cores with deep-seafloor sediments were recovered in the Trans-Atlantic Geotraverse (TAG) field along the Mid Atlantic Ridge (MAR). Sediments were analyzed on-board for physicochemical properties such as lightness (L*), pH and Eh. Selected samples were studied for mineral composition by X-ray powder diffraction (XRD). Based on XRD data, sediment samples were separated into high-, low- and non-carbonated. Removal of carbonates is a common technique in mineralogical studies in which HCl is used as the extraction agent. In the present study, sequential extraction was performed with sodium acetate buffer (pH 5.0) to remove carbonates. The ratio between the highest calcite XRD reflection in the original samples (Iorig) vs its XRD-reflection in samples after their treatment with the buffer (Itreat) was used as a quantitative parameter of calcite removal, as well as to identify minor minerals in carbonated samples (when Iorig/Itreat > 24). It was found that the lightness parameter (L*) showed a positive correlation with calcite XRD reflection in selected TAG samples, and this could be applied to the preliminary on-board determination of extraction steps with acetate buffer (pH 5.0) in carbonated sediment samples. The most abundant minerals detected in carbonated samples were quartz and Al- and Fe-rich clays. Other silicates were also detected (e.g., calcic plagioclase, montmorillonite, nontronite). In non-carbonated samples, Fe oxides and hydroxides (goethite and hematite, respectively) were detected. Pyrite was the dominant hydrothermal mineral and Cu sulfides (chalcopyrite, covellite) and hydrothermal Mn oxides (birnessite and todorokite) were mineral phases identified in few samples, whereas paratacamite was detected in the top 20 cm of the core. The present study demonstrates that portable XRD analysis makes it possible to characterize mineralogy at cored sites, in particular in both low- and high-carbonated samples, before the end of most cruises, thus enabling the quick modification of exploration strategies in light of new information as it becomes available in near-real time.

Who has the power? A reflection on teaching drama improvisation with young children - Ho, Ka Lee Carrie (Journal of Early Childhood Research, 2020)
The following study reflects and explores the dynamics of aesthetic experiences within drama improvisations. This arts-based research was carried out in Hong Kong with six Cantonese children who were aged 3?5?years. Data were collected from the video transcripts of five workshops and the researcher?s own research journal. Two significant milieus were observed: switching in-between roles and intuitive creativity is not talkback. I argue that because each of these two milieus provide the foreground for the complex ? and at times contradictory ? nature of children?s aesthetic experiences where Deleuzian power is at play, opportunities arise for both, challenging the traditional adult?child power relations, and in so doing, educators can be able to reconfigure and reconceptualise teaching goals and practices, both generally and specifically, within the context of early childhood education.

Unravelling potentials and limitations of sharing economy in reducing unnecessary consumption: A social science perspective - Lai, Michael K. W.; Ho, Amy P. Y. (Resources, Conservation and Recycling, 2020)
Hyper-consumption in capitalist economies has had a severe impact on the environment that no one can escape. In recent year, there has been a high degree of optimism in sharing economy with regard to coping with the environmental problems caused by consumption. However, most of the current literature focuses on business perspectives in which a sharing economy is portrayed as a new business model, but not as a way to curb environmental degradation. This paper, based on a social science perspective, investigates the potentials and limitations of the strategies adopted in sharing economy projects towards social transformation (especially coping with environmental degradation and hyper-consumption), with the adoption of Erik Olin Wright’s concept of real utopia. A case study approach has been adopted in terms of a sharing economy project named ‘Waste-no-mall (Yuen Long)’ in Hong Kong. The project founder embraces ideological-led strategies based on collective responsibility, self-determination and reflexivity, encouraging the participants to reflect on their consumption behaviours, and thus increasing the level of awareness of the need to reduce unnecessary consumption. However, it is a double-edge sword that limits its impact to those who are active participants, without spreading to others the need for change. It is also limited for their interstitial strategies within the project, and is unable to call for a concrete symbiotic transformation when it comes to policy. The significance of this paper is two-fold. First, it adopts a social science perspective that centres on exploring the proclaimed social implications of sharing economy, an aspect which is under-studied given that most of current studies are from a business perspective; second, it extends Wright’s concept to an operational level by showing an important pathway aiming to solve environmental problems through the simultaneous achievement of both horizontal and vertical balancing strategies, based on Wright’s concept of real utopia.
Keywords: Hong Kong; Mindful consumption; Real utopia; Sharing economy; Social transformation

The truth, the whole truth, and nothing but the truth - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

The scalpel model of educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

The Importance of Readiness for Change, a Leadership Perspective Based on a Case Study in Macau, SAR China - Marques, João; Reis, Joana; Phillips, Jenny O. L.; Diakite, Ansoumane (Journal of Advanced Management Science, 2020)

The Film Sound Analysis Framework: A Conceptual tool to Interpret the Cinematic Experience - Barbosa, Álvaro; Dizon, Kristine (Journal of Science and Technology of the Arts, 2020)
Keywords: Analysis framework; Film studies; Sound and music design

The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.

Sulfur isotopic compositions of sulfides along the Southwest Indian Ridge: implications for mineralization in ultramafic rocks - Dias, Ágata; Ding, Teng; Tao, Chunhui; Liang, Jin; Chen, Jie; Wu, Bin; Ma, Dongsheng; Zhang, Rongqing; Wang, Jia; Liao, Shili; Wang, Yuan; Yang, Weifang; et al. (Mineralium Deposita, 2020)

Statistical Forecast of Pollution Episodes in Macao during National Holiday and COVID-19 - Lei, Man Tat; Monjardino, Joana; Mendes, Luisa; Gonçalves, David; Ferreira, Francisco (International Journal of Environmental Research and Public Health, 2020)
Statistical methods such as multiple linear regression (MLR) and classification and regression tree (CART) analysis were used to build prediction models for the levels of pollutant concentrations in Macao using meteorological and air quality historical data to three periods: (i) from 2013 to 2016, (ii) from 2015 to 2018, and (iii) from 2013 to 2018. The variables retained by the models were identical for nitrogen dioxide (NO2), particulate matter (PM10), PM2.5, but not for ozone (O3) Air pollution data from 2019 was used for validation purposes. The model for the 2013 to 2018 period was the one that performed best in prediction of the next-day concentrations levels in 2019, with high coefficient of determination (R2), between predicted and observed daily average concentrations (between 0.78 and 0.89 for all pollutants), and low root mean square error (RMSE), mean absolute error (MAE), and biases (BIAS). To understand if the prediction model was robust to extreme variations in pollutants concentration, a test was performed under the circumstances of a high pollution episode for PM2.5 and O3 during 2019, and the low pollution episode during the period of implementation of the preventive measures for COVID-19 pandemic. Regarding the high pollution episode, the period of the Chinese National Holiday of 2019 was selected, in which high concentration levels were identified for PM2.5 and O3, with peaks of daily concentration exceeding 55 μg/m3 and 400 μg/m3, respectively. The 2013 to 2018 model successfully predicted this high pollution episode with high coefficients of determination (of 0.92 for PM2.5 and 0.82 for O3). The low pollution episode for PM2.5 and O3 was identified during the 2020 COVID-19 pandemic period, with a low record of daily concentration for PM2.5 levels at 2 μg/m3 and O3 levels at 50 μg/m3, respectively. The 2013 to 2018 model successfully predicted the low pollution episode for PM2.5 and O3 with a high coefficient of determination (0.86 and 0.84, respectively). Overall, the results demonstrate that the statistical forecast model is robust and able to correctly reproduce extreme air pollution events of both high and low concentration levels.
Keywords: COVID-19; air pollution; air quality forecast; modelling; national holiday; pollution episodes

Statistical Forecast Applied to Two Macao Air Monitoring Stations - Lei, M.; Monjardino, J.; Mendes, L.; Gonçalves, D.; Ferreira, F. (IOP Conference Series: Earth and Environmental Science, 2020)
The levels of air pollution in Macao often exceeded the levels recommended by WHO. In order for the population to take precautionary measures and avoid further health risks under high pollutant exposure, it is important to develop a reliable air quality forecast. Statistical models based on multiple regression (MR) analysis were developed successfully for Macao to predict the next day concentrations of PM10, PM2.5, and NO2. All the developed models were statistically significantly valid with a 95% confidence level with high coefficients of determination (from 0.89 to 0.92) for all pollutants. The models utilized meteorological and air quality variables based on five years of historical data, from 2013 to 2017. The data from 2013 to 2016 were used to develop the statistical models and data from 2017 were used for validation purposes. A wide range of meteorological and air quality variables were identified, and only some were selected as significant dependent variables. Meteorological variables were selected from an extensive list of variables, including geopotential height, relative humidity, atmospheric stability, and air temperature at different vertical levels. Air quality variables translate the resilience of the recent past concentrations of each pollutant and usually are maximum and/or the average of latest 24-hour levels. The models were applied in forecasting the next day average daily concentrations for PM10, PM2.5, and NO2 for the air quality monitoring stations. The results are expected to be an operational air quality forecast for Macao.

Review of Gorard, S. (2020) Getting evidence into education: evaluating the routes to policy and practice - Morrison, Keith (Educational Research and Evaluation, 2020)

Review of Biesta. G. (2020) Educational research: an unorthodox introduction, Educational Research and Evaluation - Morrison, Keith (Educational Research and Evaluation, 2020)

Reawakening Macanese identity: the impact of Chinese outbound tourism - Lou, Lai-Chu Ivy; Xie, Philip Feifan (Journal of Policy Research in Tourism, Leisure and Events, 2020)
The purpose of this paper examines the potential role of Chinese outbound tourism as a catalyst of change for the Macanese identity. There is an emerging trend to have a new identity amongst Macanese residents to valorize cultural and heritage assets. By using Bourdieu’s concept of habitus, it proposes that the social media space is built to voice concerns of language, place attachment and induced public participation. The study utilizes a mixed method approach comprising a survey for netizens and content analysis of online discussions, in order to fully understand changes due to Chinese outbound tourism.
Keywords: China; Identity; Macau; linguistic sensitivity; place attachment; public participation

Psychometric properties of a Chinese version of the Constructivist Learning Environment Survey among secondary-school students in Hong Kong - Kwan, Yee Wan (Learning Environments Research, 2020)
The study examined the factor structure, reliability and validity of a Chinese version of the Constructivist Learning Environment Survey (C-CLES), an instrument for assessing students’ perceptions of the extent of constructivist approaches prevalent in classrooms. A convenience sample of 967 students in Secondary Three (Grade 9) in Hong Kong participated in this study by completing a self-administered questionnaire in their class time. Exploratory and confirmatory factor analyses supported the hypothesised factor structure, indicating five theoretical constructivist environment dimensions that showed goodness-of-fit to 25 items: Personal Relevance, Uncertainty, Critical Voice, Shared Control, and Student Negotiation. Criterion-related validity, involving evidence based on relations to other variables, was assessed by correlations between the constructivist environment dimensions and cognitive strategies and academic ability. Most correlations were statistically significant and in the positive direction. The C-CLES with 25 items provides a useful measure for educational practice and research among school students.
Keywords: Cognitive outcomes; Constructivist learning environment; Secondary schools; Validation

Pestilent Popes or a Pestilent Church? Judaism, Catholicism, and Skeptical Theism - McNabb, Tyler Dalton (The Heythrop Journal, 2020)

Parental stress and parenting in Chinese immigrant families: The mediating role of social support - Liu, Shu-Wen; Zhai, Fuhua; Gao, Qin (Child & Family Social Work, 2020)
Abstract As the population of Chinese immigrants has been growing rapidly in the United States, it has been understudied on the parenting behaviours as well as the roles parental stress and social support playing in parenting in this group. This study investigated whether parental stress was associated with parenting and whether this relationship was mediated by social support in a sample of 255 Chinese immigrant parents from the Survey of Asian American Families in New York City. Regression analyses with a rich array of control variables found that a higher level of parental stress and the presence of one or more stressors such as unemployment, low income, and low education were positively associated with the use of harsh discipline and parent?child conflicts and negatively associated with positive parenting practices. Social support functioned as a significant mediator in the relationships between parental stress and positive parenting practices but not in the relationships of parental stress with parent?child conflict or the use of harsh discipline.
Keywords: Chinese immigrants; harsh discipline; parental stress; parenting practices; parent–child conflict; social support

On the probability flow in the Stock market I: The Black-Scholes case - Arraut, Ivan; Au, Alan; Tse, Alan Ching-biu; Marques, Joao Alexandre Lobo (arXiv.org, 2020)
It is known that the probability is not a conserved quantity in the stock market, given the fact that it corresponds to an open system. In this paper we analyze the flow of probability in this system by expressing the ideal Black-Scholes equation in the Hamiltonian form. We then analyze how the non-conservation of probability affects the stability of the prices of the Stocks. Finally, we find the conditions under which the probability might be conserved in the market, challenging in this way the non-Hermitian nature of the Black-Scholes Hamiltonian.
Keywords: General Finance

Nonlinear characterization and complexity analysis of cardiotocographic examinations using entropy measures - Marques, J.A.L.; Cortez, P.C.; Madeiro, J.P.V.; Albuquerque, V.H.C.; Fong, S.J.; Schlindwein, F.S. (Journal of Supercomputing, 2020)

Noise-induced hearing loss in zebrafish: investigating structural and functional inner ear damage and recovery - Breitzler, Lukas; Lau, Ieng Hou; Fonseca, Paulo J.; Vasconcelos, Raquel O. (Hearing Research, 2020)
Exposure to continuous moderate noise levels is known to impair the auditory system leading to Noise-Induced Hearing Loss (NIHL) in animals including humans. The mechanism underlying noise-dependent auditory Temporary Threshold Shifts (TTS) is not fully understood. In fact, only limited information is available on vertebrates such as fishes, which share homologous inner ear structures to mammals and have the ability to regenerate hair cells. The zebrafish Danio rerio is a well-established model in hearing research providing an unmatched opportunity to investigate the molecular and physiological mechanisms of NIHL at the sensory receptor level. Here we investigated for the first time the effects of noise exposure on TTS and functional recovery in zebrafish, as well as the associated morphological damage and regeneration of the inner ear saccular hair cells. Adult specimens were exposed for 24h to white noise at various amplitudes (130, 140 and 150 dB re. 1 μPa) and their auditory sensitivity was subsequently measured with the Auditory Evoked Potential (AEP) recording technique. Sensory recovery was tested at different times post-treatment (after 3, 7 and 14 days) and compared to individuals kept under quiet lab conditions. Results revealed noise level-dependent TTS up to 33 dB and increase in response latency. Recovery of hearing function occurred within 7 days for fish exposed to 130 and 140 dB noise levels, while fish subject to 150 dB only returned to baseline thresholds after 14 days. Hearing impairment was accompanied by significant loss of hair cells only at the highest noise treatment. Full regeneration of the sensory tissue (number of hair cell receptors) occurred within 7 days, which was prior to functional recovery. We provide first baseline data of NIHL in zebrafish and validate this species as an effective vertebrate model to investigate the impact of noise exposure on the structure and function of the adult inner ear and its recovery process.
Keywords: Fish; Hair cells; Hearing sensitivity; Noise; Sound pressure level; Temporary threshold shift

Multilingual freedom of the press in Macau - Simões, José Manuel; Mayes, Lee ([RMd] RevistaMultidisciplinar, 2020)
There can be no conclusive determining regarding true press freedom in Macau, and perhaps this statement can be applied elsewhere as well. Issues of self-censorship, partisanship, or cultural loyalty exist in cities and countries around the world, and most of the time there is simply no reliable measurement to determine their impact. The Special Administrative Region (SAR) of Macau is separate and distinct from mainland China, but that does not mean that it is entirely without question regarding its freedom of the press, ethical journalistic practices, and interference by non-authorized agencies at the three languages local newspapers.
Keywords: autocensura; ingerência; liberdade de imprensa; partidarismo; práticas éticas

Multi-view convolutional neural network with leader and long-tail particle swarm optimizer for enhancing heart disease and breast cancer detection - Lan, K.; Liu, L.; Li, T.; Chen, Y.; Fong, S.; Marques, J.A.L.; Wong, R.K.; Tang, R. (Neural Computing and Applications, 2020)

Methods, understandings, and expressions of causality in educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

Mary and Fátima: A Modest C-Inductive Argument for Catholicism - Mcnabb, Tyler Dalton; Blado, Joseph E. (Perichoresis, 2020)
AbstractC-Inductive arguments are arguments that increase the probability of a hypothesis. In this paper, we offer a C-Inductive argument for the Roman Catholic hypothesis. We specifically argue that one would expect the Miracle of Fátima on Roman Catholicism more so than on alternative hypotheses. Since our argument draws on confirmation theory, we first give a primer for how confirmation theory works. We then, provide the historical facts surrounding the Miracle of Fátima. We offer up two competing naturalistic explanations that attempt to explain the historical facts, but then, argue that a supernatural explanation is superior. Having established that something miraculous likely occurred at Fátima, we move to argue for the overall thesis of the paper. Finally, we engage several objections to our argument.

Inclusive Education Teachers—Strategies of Working Collaboratively With Parents of Children With Special Educational Needs in Macau - Ng, Shun Wing; Kwan, Yee Wan (International Journal of Educational Reform, 2020)
Education for learners with special education needs has become one of the major concerns of education policies in every corner of the world. In Macau, however, the transformation of schools into inclusive environments is reported to be slow because many teachers in Macau have not accepted the key values of inclusive education and possess little knowledge of their responsibilities as inclusive education teachers. Despite being nonempirical, the aim of this article is twofold: to inform inclusive education teachers, especially those in Macau and other developing regions, of the necessary knowledge, skills and strategies of working collaboratively with parents of children with SEN and provide policy makers concerned with practical ideas of designing effective professional development programmes for teachers working in the inclusive environment. The ultimate aim is to ensure that children with SEN benefit from an education process that includes quality learning opportunities.

High-precision geochronology of Mesozoic magmatism in Macao, Southeast China: Evidence for multistage granite emplacement - Quelhas, Pedro; Dias, Ágata; Mata, João; Davis, Donald Wayne; Ribeiro, Maria Luísa (Geoscience Frontiers, 2020)

Health and Well-Being Education: Extending the SCARF Learning Analytics Model for Identifying the Learner Happiness Indicators - Li, Tengyue; Marques, Joao Alexandre Lobo; Fong, Simon (International Journal of Extreme Automation and Connectivity in Healthcare (IJEACH), 2020)
The use of learning analytics (LA) in real-world educational applications is growing very fast as academic institutions realize the positive potential that is possible if LA is integrated in decision making. Education in schools on public health need to evolve in response to the new knowledge and th...

Has Oppy Done Away with the Aristotelian Proof? - McNabb, Tyler; DeVito, Michael (The Heythrop Journal, 2020)

Group work and cultural characteristics in a Chinese school - Morrison, Keith; Garcia, Alejandro Salcedo; Wong, Sin Teng (Educational Research and Evaluation, 2020)

Evaluation of mathematical models for QRS feature extraction and QRS morphology classification in ECG signals - do Vale Madeiro, João Paulo; Lobo Marques, João Alexandre; Han, Tao; Coury Pedrosa, Roberto (Measurement, 2020)
It is plausible to assume that the component waves in ECG signals constitute a unique human characteristic because morphology and amplitudes of recorded beats are governed by multiple individual factors. According to the best of our knowledge, the issue of automatically classifying different ’identities’ of QRS morphology has not been explored within the literature. This work proposes five alternative mathematical models for representing different QRS morphologies providing the extraction of a set of features related to QRS shape. The technique incorporates mechanisms of combining the mathematical functions Gaussian, Mexican-Hat and Rayleigh probability density function and also a mechanism for clipping the waveform of those functions. The searching for the optimal parameters which minimize the normalized RMS error between each mathematical model and a given QRS search window enables to find an optimal model. Such modeling behaves as a robust alternative for delineating heartbeats, classifying beat morphologies, detecting subtle and anomalous changes, compression of QRS complex windows among others. The validation process evaluates the ability of each model to represent different QRS morphology classes within 159 full ECG signal records from QT database and 584 QRS search windows from MIT-BIH Arrhythmia database. From the experimental results, we rank the winning rates for which each mathematical model best models and also discriminates the most predominant QRS morphologies Rs, rS, RS, qR, qRs, R, rR’s and QS. Furthermore, the average time errors computed for QRS onset and offset locations when using the corresponding winner mathematical models for delineation purposes were, respectively, 12.87±8.5 ms and 1.47±10.06 ms.
Keywords: ECG feature extraction; Mathematical modeling; Morphology classification; QRS complex delineation

Enhancing Student Learning and Teacher Development: Does “Assessment for Learning” Matter? - Ng, Shun Wing; Kwan, Yee Wan; Huey Lei, Ka Hio (International Journal of Educational Reform, 2020)
This paper aims to report a case study of exploring the effect of ?assessment for learning? on improving student learning and facilitating teachers? professional development in the examination-oriented context of Hong Kong. By adopting Variation Theory of the Lesson Study approach, data were collected through pre- and post-tests, interviews with students and teacher participants and observation field-notes in order to help diagnose students? learning difficulties and provide evidence for teachers to refine their teaching strategies to enhance students? learning effectiveness. The students? improvement in learning performance informed the teacher participants of the usefulness of ?assessment for learning? in the classroom.

Editorial: On Cinema - Ribas, Daniel; Crespo, Nuno; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2020)
In the past decades, the field of cinema has undergone several transformations. The digital turn increasingly called for new forms of production, distribution, and exhibition, which imply different ways of thinking, doing, and experimenting cinema. These new forms also reduced the gap between cinema to other so-called visual arts. If cinema and visual arts were already in the process of merging, the last years forced the naturalization of thinking in similar theoretical grounds. This special issue aims to be a forum for the discussion of new practices of researching cinema, and the changes in cinema’s forms of experience and production.
Keywords: Art and cinema; Cinema; Contemporary cinema; Digital turn; Visual Arts

Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students - Caires, C. S.; Barbosa, A.; Hanyou, W. (International Journal of Educational and Pedagogical Sciences, 2020)
Design for Classroom Units: A Collaborative Multicultural Studio Development with Chinese Students

Crowdsensing-Based Gamification for Collective Assistance for Post-Era of Coronavirus Epidemic in Community Living - Luo, Renfei; Marques, João Alexandre Lôbo; Ong, Kok-Leong; Fong, Simon (International Journal of Extreme Automation and Connectivity in Healthcare (IJEACH), 2020)
Crowdsensing exploits the sensing abilities offered by smart phones and users' mobility. Users can mutually help each other as a community with the aid of crowdsensing. The potential of crowdsensing has yet to be fully realized for improving public health. A protocol based on gamification to encoura...

Are Work Engaged Employees Perceive Career Success? A Study of Hospitality at Macau - Kuok, A. C. H (Journal of Hospitality, 2020)
This study examined 206 casino dealers in hospitality at Macau to investigate the extent of their subjective career success and work engagement. Casino dealers were work engaged, but their subjective career success was fairly low, with significant difference between them, which indicates they have cognitive dissonance about their jobs. Several personality variables (emotional suppression and work ethic), organizational variables, i.e., organizational socialization (training, understanding, coworker support, future prospects), and distributive justice, were assessed in relation to subjective career success and work engagement. Organizational socialization, work ethic, and distributive justice were positively correlated with and predictors of subjective career success and work engagement; while emotion suppression was negatively correlated with and predictor of work engagement. This study provides evidence of extending the theories of subjective career success and work engagement in Chinese society and hospitality. Also, it identifies factors that could resolve the employees’ cognitive dissonance, and implementations for management were discussed.
Keywords: Subjective career success; emotion suppression; hospitality; human resources; socialization; work engagement

Anxious immobilities: an ethnography of coping with contagion (Covid-19) in Macau - Zuev, Dennis; Hannam, Kevin (Mobilities, 2020)
In February 2020, Macau became one of the first regions where the pandemic of coronavirus or Covid-19 affected the totality of social and economic life leading to increased anxieties over movement and distance. Although Macau has had very few actual cases of the virus – 46 in total –and no deaths from it, the Macau government rapidly instituted a lock down. The aim of this article is to reflect on how the social experience of being in lockdown can provide insights into understanding the type of experience or condition that we provisionally term ‘anxious immobility.’ Such a condition is characterized by a total disruption of everyday rhythms and specifically anxious waiting for the normalization of activity while being the subject of biosocial narratives of quarantine and socially responsible. The paper is based upon 3 months of ethnographic research conducted by two researchers based in Macau. We also reflect upon some aspects of the politics of mobilities in the light of disruptions and friction points between Hong Kong, Macau, mainland China, and the rest of the world.

Anticipare il Futuro della Cina. L’eredità del vescovo gesuita Jin Luxian SJ (“Anticipating the Future of China. The Heritage of the Jesuit Bishop Jin Luxian SJ”) - Rothlin, Stephan (La Civiltà Cattolica, 2020)

Analysis of reading errors in Portuguese : digraphs and complex syllabic structures - Simões, Edlia; Martins, Margarida Alves (Análise Psicológica, 2020)
Abstract: The Portuguese language poses several challenges for children in the initial phase of learning how to read, particularly in the case of letters that may correspond to more than one phoneme, two letters that correspond to a single phoneme and in the case of words containing complex syllabic structures. The objective of this study was to perform a psycholinguistic analysis of the reading errors of children, attending the 1st (n=175) and 2nd year (n=137) of schooling, specifically in the case of words containing digraphs or complex syllabic structures and to analyse the differences between children’s reading errors in these two years. An oral reading test was used for data collection. A quantitative and qualitative analysis of the type of reading errors was conducted using words with consonant digraphs (ch, nh, lh, gu, rr, ss), and words with complex syllables <CVC and CCV>. This analysis showed that children presented greater difficulties in some specific digraphs and tended to simplify complex syllables, either by adding or deleting phonemes. The quantity and quality of the reading errors of children attending both grades were discussed in light of reading acquisition theories and children’s phonological development.